2019
DOI: 10.4018/978-1-5225-7362-3.ch004
|View full text |Cite
|
Sign up to set email alerts
|

An Extension to the Delone and Mclean Information Systems Success Model and Validation in the Internet Banking Context

Abstract: The modern internet era opened a plethora of opportunities for doing business online. Internet banking (IB) is one such innovation that made great strides from its humble beginnings in the mid-1990s. It is important for bank practitioners to know the factors contributing to the success of new technology by customers to enable them to be better placed in the competitive segment. This study proposes an extension to the Delone and Mclean IS success model to evaluate information systems(IS) success in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The mixed results imply that the model can assist in identifying the success variables in different settings as shown in the results obtained by Iivari (2005) and Jagannathan et al (2018). In the case of the internet banking application, security and information quality are expected to be the determining factors for IS success which was the case in Jagannathan et al's (2018) study and in the mandatory setting system quality and information quality would have little effect on the use as it is mandatory to use the system irrespective of the quality antecedents..…”
Section: Figure 2 Updated Delone and Mclean Is Success Model (Delonementioning
confidence: 91%
See 3 more Smart Citations
“…The mixed results imply that the model can assist in identifying the success variables in different settings as shown in the results obtained by Iivari (2005) and Jagannathan et al (2018). In the case of the internet banking application, security and information quality are expected to be the determining factors for IS success which was the case in Jagannathan et al's (2018) study and in the mandatory setting system quality and information quality would have little effect on the use as it is mandatory to use the system irrespective of the quality antecedents..…”
Section: Figure 2 Updated Delone and Mclean Is Success Model (Delonementioning
confidence: 91%
“…For instance, Hsu, Chang, Chu, & Lee (2014) extended the model by adding the trust variable in the context of e-commerce. Similarly, Jagannathan, Balasubramanian, and Natarajan (2018) employed the model by adding security as a construct in a study to examine the acceptance of internet banking. Other authors have focused on validating the model in e-commerce (DeLone & McLean, 2004), Knowledge Repository Systems (Qian & Bock, 2005), eGovernment systems (Wang & Liao, 2008), and a mandatory information system (Iivari, 2005).…”
Section: Figure 2 Updated Delone and Mclean Is Success Model (Delonementioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that in a mandatory setting of an IS, irrespective of the quality antecedents, the SQ and IQ would have no or little effect on SU (Iivari, 2005;Jagannathan et al, 2018;Lwoga, 2012;Yakubu & Dasuki, 2018). This study supports this notion, as no significant link was found between SQ and SU, or between IQ and SU.…”
Section: Discussionmentioning
confidence: 99%